(untitled) (Journal of Human Sciences, 2023)
Computational linguistics has produced linguistic theories that are associated with computers, and has sought to program language electronically and establish specialized dictionaries and machine translation. This has also produced a range of terms associated with the research methodology, including the term "classificatory nouns," which is a linguistic mechanism used in the development of electronic dictionaries. This term has appeared in computational linguistics, especially in the theory of Maurice Gross’s grammatical dictionary and in the theory of semantic categories of Gaston Gross, which is a derivative of the former. Both theories focus on the development of electronic dictionaries. This study aims to shed light on this linguistic mechanism, not only from a theoretical perspective but also from an applied perspective. We explore the issue of classification for nouns in the Arabic dictionary, both old and modern, by examining examples such as "food" to highlight how they are used, supported, and intersect with each other, and to distinguish between the noun in the observed usage and the classificatory noun.